Dampak Publikasi Pelaporan Keuangan Ganda Bank Lippo terhadap Harga Saham Perbankan di Bursa Efek Jakarta - Dewi Amalia (Jurnal Akuntansi dan Bisnis, 2004)
This study is purposed to examine the influence of publication of the Lippo Bank dual financial reports to the stock prices reaction, by applying the event-study methodology to analyse the market reaction on the daily closing price of 24 stocks banks that listing in Jakarta Stock Exchange. The results of analysis (using t-test) show that the publication of the Lippo Bank dual financial reports has not given effects which is significantly influence the stock prices. It’s mean that applying financial reports principles have not been a fundamental driver stock exchange in Indonesia. Comparing the stock prices before and after the publication are not significantly different. This market reaction show that public have not capable enough to use the publication of the Lippo Bank dual financial reports as a signal (good or bad news) to evaluate the future prospect of the firm.